Feasibility of Cyclodextrin-Potassium Ion Assemblies Synthesis and Its Application in Loading Bio-active Molecules. - Perez, Yomkippur
In the study, colorless cubic crystals of ?green? cyclodextrin (CD)-based assemblies were synthesized and their potential to load bio-active molecules such as drugs and, separately, enzymes were investigated. Busulfan (Bu), an anti-cancer drug widely used to treat chronic myelogenous leukemia (CML), was used as a test drug while trypsin and lipase were used as model enzymes. These porous CD-K+ ion assemblies were prepared by dissolving alkali metal salts and γ-CD in water followed by vapor diffusion in varying solvents for several days. Crystals were activated via dichloromethane dispersion and in vacuo drying. Slow vapor diffusion with ethanol was found to give the highest yield and fastest crystallization time among all the solvents used. The materials synthesized using ethanol were characterized to be cubic crystals with sizes ranging from 100?1000 µm that are stable up to 250 °C. Loading of Bu (%S) onto the CD-K+ ion assemblies and co-crystallization with trypsin (%N) were both successful, as confirmed by elemental analysis. Loading studies of Bu performed using thermogravimetric analysis (TGA) confirmed about 5 wt% loading in the porous materials.